2013
DOI: 10.2217/whe.13.17
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Childbirth and Pelvic Floor Disorders

Abstract: Childbirth is an important event in a woman’s life. Vaginal childbirth is the most common mode of delivery and it has been associated with increased incidence of pelvic floor disorders later in life. In this article, the authors review and summarize current literature associating pelvic floor disorders with vaginal childbirth. Stress urinary incontinence and pelvic organ prolapse are strongly associated with vaginal childbirth and parity. The exact mechanism of injury associating vaginal delivery with pelvic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
2
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 98 publications
6
101
2
7
Order By: Relevance
“…This incidence is related to vaginal delivery and parity which cause pelvic floor dysfunction. 11 Boyles et al showed that the first labor influenced the most towards the mechanism of continence. 12 However, it was still questioned whether caesarean section could prevent pelvic floor trauma.…”
Section: Resultsmentioning
confidence: 99%
“…This incidence is related to vaginal delivery and parity which cause pelvic floor dysfunction. 11 Boyles et al showed that the first labor influenced the most towards the mechanism of continence. 12 However, it was still questioned whether caesarean section could prevent pelvic floor trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mechanism behind this remains unknown but it has been linked to the nature of a woman's urinary system and childbirth as well as perineal trauma and denervation. (2) Cesarean section is certainly done in order to avoid complications that could lead to losing the mother and/or the baby. Cesarean section is not better than vaginal reproduction since in vaginal reproduction the mother recovers quicker.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Various means of delivery have been linked to the chances of the mother to develop urinary incontinence. (2) According to Rogers stress incontinence is common in women who have given vaginal birth as it leads to pelvic floor muscle destruction. (3) The chances to develop various forms of incontinence like stress incontinence and urge incontinence are higher in women who had vaginal delivery as compared to those who had cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…12 Namun, studi Boyles menunjukkan bahwa berat lahir bayi tidak berpengaruh terhadap risiko kejadian IU pada subjek yang dilakukan seksio sesaria, namun berat lahir bayi ≥4000 gr pada persalinan pervaginam akan meningkatkan risiko kejadian IUT dengan OR 1,22 (IK95% 1,03-1,45). 18 Pada penelitian ini didapatkan pula bahwa risiko kejadian IU pascapersalinan dipengaruhi oleh lama kala dua yang dikategorikan >60 menit dan <60 menit (p<0,05).…”
Section: Analisis Bivariatunclassified
“…Inkontinensia urin tekanan merupakan inkontinensia urin yang berhubungan dengan aktivitas fisik, didefinisikan sebagai keluarnya urin yang tidak terkendali saat beraktifitas, bersin atau batuk. 11 Inkontinensia urin tekanan dan prolaps organ panggul adalah kelainan yang umum terjadi dan memerlukan operasi perbaikan pada 11% perempuanmenjelang usia 80 tahun, 12 dengan kemungkinan operasi ulang sebesar 30%. 13 Kelainan ini berhubungan erat dengan persalinan pervaginam dan paritas yang mengakibatkan terjadinya disfungsi dasar panggul.…”
unclassified